Differences of patient empowerment between elective and contracted physicians in internal medicine in Austria: a quantitative content analysis - Bettina Simetsberger; Manfred Pferzinger; Martin K. J. Waiguny (BMC Health Services Research)
Abstract Background Physicians impact and promote patient empowerment at various levels. Elective or contracted physicians uniquely provide specialised ambulatory care in Austria. The difference between the two groups is due to the contractual relationship with the social health insurance providers. This paper researches whether there are differences in the promotion of patient empowerment between elective and contracted physicians in internal medicine in Vienna based on four dimensions of patient empowerment. Methods A quantitative content analysis analyses the comments on DocFinder.at to identify the differences between the two groups. A deductive-inductive approach based on literature and comments from DocFinder.at led to a codebook with seven categories and forty-eight variables. We collected a total of 1,153 comments, and 912 of them are relevant for further analysis. Differences between elective and contracted physicians became evident through defined dimensions of patient empowerment. Results In the health literacy dimension, elective physicians apply relationship-relevant factors more effectively. They are also more successful in ensuring that patients feel adequately informed. No significant differences were found in the dimension of shared decision-making, but the discussion of treatment options correlated strongly with the amount of time spent by a physician. In the self-management dimension, elective physicians provide more precise and detailed explanations, highlighting their ability to foster better self-management. Differences in the communication dimension favour elective physicians at both factual and interpersonal levels, although there are no significant differences in patient’s ability to ask questions and receive answers. Across all dimensions, the time spent with patients emerges as a crucial factor influencing patient empowerment. Conclusions The findings open up several avenues for further research, offering an initial understanding of the differences in patient empowerment between elective and contracted physicians. The results reveal that elective physicians are more likely to create a supportive environment for patient empowerment, underscoring the crucial role of physician-patient interactions in this process. However, given the limitations of the current methods, future research could explore these differences through alternative approaches, such as surveys or interviews, to provide a more comprehensive understanding.